Pelatihan Digital Marketing pada Produsen Sabun Cuci Piring Rumahan di Kebumen - Saryatun Saryatun; Joko Purnomo; Subur Yuswanto; Eko Pria Kusuma (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This community development activity aims to help MSMEs penetrate the digital market. Team provided digital marketing training to the home dishwashing soap industry on December 17, 2023, at Gemintang Café and Resto. Fifteen participants, all dishwashing soap producers from Kebumen Regency, attended. The training aimed to increase product sales through lectures, practice sessions, and Q&A. The one-day event covered product photography, online marketing techniques, and market expansion strategies. Participants were highly enthusiastic and actively engaged with the material. They learned to take attractive product photos, identify suitable marketplaces, and use marketing tricks on platforms like WhatsApp, Facebook, Instagram, and TikTok. The training also highlighted new cooperation opportunities with agencies and institutions, contingent on having legal and accountable permits.